A Study on Muscle Fatigue Associated with Awkward Posture among Workers in Aerospace Industry - Kamat, Seri Rahayu; Norhidayah, Hashim; Mohd Shahrizan, Othman (Trans Tech Publication, Switzerland, 2013)
In aerospace industry, many tasks required manufacturing workers to perform their works in awkward posture. Awkward posture is a practical working posture when joints are not in neutral position such as lifting heavy products, reaching materials, bending forward their back when doing jobs, and pushing or pulling excessive loads because those tasks require a stable position and large degree of freedom. If the workers perform the jobs continuously in awkward posture throughout the working hours, they may be experience muscle fatigue. The objective of this study is to measure the myoelectric level (μV) exerted by the right and left thoracolumbar fascia muscles while workers perform the lay-up process in aerospace industry. The myoelectric level in the muscles was measured using surface Electromyography (sEMG) measurement. Six production workers from aerospace industry participated as subjects. The muscle fatigue of the subjects was measured during beginning until finish of lay-up process. This measuring activity has been doing from Wednesday to Friday. Highest results of myoelectric level for right thoracolumbar fascia is when the workers make the lay-up process for ply seven until ply eleven. Different with the results of myoelectric level for left thoracolumbar fascia which is; three of the workers got highest result when they are making the lay-up process for ply seven until ply eleven, but the other three of the workers got highest result when they are making the lay-up process for ply twelve. Nevertheless, after averaging both of the results, a mean result for each worker shows the highest myoelectric level is when the workers make the lay-up process for ply seven until ply eleven. According to the mean, a percentage of worse tasks are projected. Based on this study, the authors concluded that muscle fatigue of the lay-up workers in aerospace industry was influenced by the work load, work activity and duration of awkward posture.